Kepatuhan Penderita Diabetes Mellitus Dalam Melaksanakan Diet Dan Terapi Olahraga - Rendita Dwibarto (Ilmiah Institut Citra Internasional, 2022)
The implementation of the DM diet is indirectly influenced by the results of education, sources of information and mass media. The success rate in the treatment of DM depends on the patient. DM sufferers at the Pundong Health Center said that special pronal exercises for DM patients have been carried out every week but are sometimes less effective because the specified schedule is not in accordance with the family who delivers and there are also several factors that prevent patients from coming to take prolanis exercise that has been scheduled by health workers. one of which is in the puskesams is Family Support. This type of research method uses quantitative with a cross sectional design. The sampling technique used was purposive sampling with a total of 36 respondents and used a questionnaire measuring instrument. Data analysis using univariate with frequency distribution and bivariate with chi square test. The results of the analysis showed the influence of knowledge, attitudes, support from officers, family support on the behavior of DM sufferers in carrying out diet and exercise therapy for DM in the work area of ​​the Pundong Health Center Yogyakarta using chi square with p values ​​of 0.032, 0.008, 0.002, 0.029 which indicates that p value < 0.005.there is an influence between knowledge, attitude, support from health workers, family support on the behavior of DM patients in carrying out diet and exercise therapy for DM in the work area of ​​the Pundong Health Center Yogyakarta.